2020
DOI: 10.1136/bmjopen-2019-034427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of basic public health service project on neonatal health services and neonatal mortality in China: a longitudinal time-series study

Abstract: ObjectiveTo analyse the trend change and level change of neonatal health services and neonatal mortality before and after the introduction of the Basic Public Health Service (BPHS) project in 2009.Design and settingA national longitudinal study on neonatal mortality from 1991 to 2017 and neonatal health services from 2000 to 2017 was conducted based on data extracted from the National Neonatal Mortality Surveillance System and National Health Statistic Yearbook. The segmented linear regression model was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…Also, the trend change in household consumption after the FMHC policy was negative and statistically significant suggesting that the FMHC policy lead to a reduction in household consumption expenditure. This result is consistent with Lagarde (2012) and Zhao et al (2020) who also found annual trend change coefficient to be negative.…”
Section: The Segmented Linear Regressionsupporting
confidence: 91%
See 2 more Smart Citations
“…Also, the trend change in household consumption after the FMHC policy was negative and statistically significant suggesting that the FMHC policy lead to a reduction in household consumption expenditure. This result is consistent with Lagarde (2012) and Zhao et al (2020) who also found annual trend change coefficient to be negative.…”
Section: The Segmented Linear Regressionsupporting
confidence: 91%
“…The segmented regression analysis helps to control for secular trends and also adjust for potential serial correlation of the data (Lagarde, 2012;Ramsey et al, 2001;Wagner et al, 2002;Zhao et al, 2020). Zhao et al (2020) used this method and analyzed the trend change and level change of neonatal health services (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) and neonatal mortality rates before and after the introduction of the Basic Public Health Service (BPHS) project in China. In addition, Lagarde (2012) used a segmented regression model and assessed the impact of health policy change on the number of monthly outpatient consultations for before and after the policy.…”
Section: Econometric Model (Second Objective)mentioning
confidence: 99%
See 1 more Smart Citation
“…Research on rural areas found that NBPHS could improve health consciousness among rural residents [16]. Moreover, it is associated with an increased volume of neonatal health services and reduced neonatal mortality [17]. For internal migrants, NBPHS can enhance their willingness for a long stay [18].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have analysed the health-related changes in the EE before and after implementing the policies. Zhao et al found that the essential public health service project had a positive impact on neonatal health services and in reducing neonatal mortality [ 17 ]. Sia et al and Druetz et al considered that the free health care policy characterised by free consultation, care, medication and laboratory and radiological examinations (including ultrasounds) implemented in 2016 in Burkina Faso had increased the usage of health services for children aged under 5 years [ 18 , 19 ].…”
mentioning
confidence: 99%